Agrobiodiversity of Kuttanad wetlands in the context of promising agroforestry practices and resource sustainability - Alexander, T. (Indian Journal of Agroforestry, 2020)
The Kuttanad wetland system in Kerala is very special by virtue of the fact that it is located 1.0-2.5 m below mean sea level and that it has a poor tree wealth, but an extensive area for cultivation of wetland crops, especially paddy and coconut. However, there are home-gardens which provide an idea of local knowledge on plant resource management offering directions to develop agroforestry systems suited to the whole wetland system. A study was undertaken to analyze the plant wealth of Kuttanad wetlands, with particular reference to home-garden and bund based agroforestry practices in terms of species composition, diversity, utilization potential and preferences by the local community. The results of documentation and subsequent analysis revealed the potential for systematic development of agroforestry in the wetland system involving plant resources such as timber trees (84); fire wood and soft wood trees (61); fibre (8), paper and pulp yielding resources (9); spices (17), beverages (2), vegetable crops (33); medicinal plants (157); fencing plants (30) and a host of other plant resource which are sustainably advantageous to the local population. The study led to the identification of promising agroforestry species suited to the wetlands, which are ecologically compatible and economically viable.